Research on the Crucial Technology in Virtual Training System of Engineering Equipment - Li Hongwei; Yang Xiaoqiang; Xue Jinhong; Jiang Tianhe (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The virtual training system involves a large number of technical problems which affect the promotion and application in our country. In this work, several key techniques for the development of engineering equipment virtual training system are addressed. Firstly, the reconstruction method for three views of machine parts is proposed based on rapid 3D surface fitting as well as NURBS composite surface. Then, the interactive control techniques for the 3D visualization interactive assembly are studied in detail. The key technology of collision detection is also illuminated in the last part. The entire engineering equipment support training system, that includes structure expressing, principle demonstration, panoramic roaming, disassembly training as well as maintenance and repair training, is developed. This facilitates the trainees in learning the support training procedures step by step, and quickly improves their technical skills. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2052